ChannelsDB: database of biomacromolecular tunnels and pores - Pravda, Lukáš; Sehnal, David; Svobodová Vareková, Radka; Navrátilová, Veronika; Toušek, Dominik; Berka, Karel; Otyepka, Michal; Koca, Jaroslav (Nucleic acids research, 2018)
ChannelsDB (http://ncbr.muni.cz/ChannelsDB) is a database providing information about the positions, geometry and physicochemical properties of channels (pores and tunnels) found within biomacromolecular structures deposited in the Protein Data Bank. Channels were deposited from two sources; from literature using manual deposition and from a software tool automatically detecting tunnels leading to the enzymatic active sites and selected cofactors, and transmembrane pores. The database stores information about geometrical features (e.g. length and radius profile along a channel) and physicochemical properties involving polarity, hydrophobicity, hydropathy, charge and mutability. The stored data are interlinked with available UniProt annotation data mapping known mutation effects to channel-lining residues. All structures with channels are displayed in a clear interactive manner, further facilitating data manipulation and interpretation. As such, ChannelsDB provides an invaluable resource for research related to deciphering the biological function of biomacromolecular channels.
Keywords: Software; software; Catalytic Domain; exprese genu; Humans; prokaryotické buňky; Gene Expression; Static Electricity; iontové kanály; Nuclear Pore; Hydrophobic and Hydrophilic Interactions; mutace; eukaryotické buňky; koenzymy; databáze proteinů; Coenzymes; lidé; zvířata; statická elektřina; aminokyseliny; Amino Acids; Prokaryotic Cells; cytochrom P-450 CYP2D6; Databases, Protein; katalytická doména; Cytochrome P-450 CYP2D6; Ion Channels; Animals; Mutation; jaderný pór; Eukaryotic Cells; hydrofobní a hydrofilní interakce